2019
DOI: 10.1016/j.ebiom.2019.03.028
|View full text |Cite
|
Sign up to set email alerts
|

Alternative splicing of the tumor suppressor ASPP2 results in a stress-inducible, oncogenic isoform prevalent in acute leukemia

Abstract: Background Apoptosis-stimulating Protein of TP53-2 ( ASPP2 ) is a tumor suppressor enhancing TP53-mediated apoptosis via binding to the TP53 core domain. TP53 mutations found in cancers disrupt ASPP2 binding, arguing for an important role of ASPP2 in TP53-mediated tumor suppression. We now identify an oncogenic splicing variant, ASPP2κ , with high prevalence in acute leukemia. Methods An mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 37 publications
2
28
0
Order By: Relevance
“…Accumulating evidence implicates aberrant AS events as the hallmarks of carcinogenesis, including tumor growth, angiogenesis, immune evasion, and metastasis [ 13 15 ]. AS promotes tumor progression not only by activating oncogene isoforms such as VEGFA but also through facilitating the degradation of suppressor genes such as TP53 [ 16 , 17 ]. AS events are also accurate predictive markers for various cancer types, including breast, lung, colorectal, and liver [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence implicates aberrant AS events as the hallmarks of carcinogenesis, including tumor growth, angiogenesis, immune evasion, and metastasis [ 13 15 ]. AS promotes tumor progression not only by activating oncogene isoforms such as VEGFA but also through facilitating the degradation of suppressor genes such as TP53 [ 16 , 17 ]. AS events are also accurate predictive markers for various cancer types, including breast, lung, colorectal, and liver [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Protein phosphatase 3 regulatory factor subunit 1 (PPP3R1) is a member of β-regulatory subunit family of calcineurin that codes for apoptosis-stimulating protein of p53 (ASPP) in the p53 integrin family [ 55 ]. The ASPP enhances P53-mediated apoptosis by binding to the P53 core domain [ 56 ]. However, the specific molecular mechanisms of the differentially expressed genes in the pathways have not been established.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis-stimulating Protein of TP53-2 (ASPP2) is a tumor suppressor enhancing TP53-mediated apoptosis. It has been found that a splice variant ASPP2κ is overexpressed in AML and displays anti-apoptotic function, therefore supporting proliferation of the cells [54].…”
Section: Alternative Splicingmentioning
confidence: 99%